Programmatic assessment of student experiences using a longitudinal survey - Draugalis JR; Plaza CM (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Objectives: The purpose of this study was to gather longitudinal data on a pharmacy class cohort concerning programmatic components as well as develop a profile of student experiences as they progress through the curriculum.Methods: The Class of 2006 (n = 67) completed a 2 page instrument at the conclusion of the first 3 professional years (PY) concerning hours spent in various activities, overall quality of various programmatic components, relationships with others in the college, and employment information. During senior week, a more extensive exit survey was administered.Results: At the conclusion of PY1, 56.5% of the class was working as a pharmacy intern. By PY3 this increased to 88.1% with a decrease to 65.7% in the final year. The hourly range of hours worked followed the same pattern. The rating of Dean's Office Staff and interactions with faculty members remained constant across all 4 years. In the final exit survey the 2 lowest rated program components were the quality of the interaction with assigned faculty advisor and the availability of professional electives. There was no difference across the professional years for the quality of relationships with staff or faculty; however, the mean rating of the quality of relationships with other students was higher for PY4 when compared to PY1.Conclusions: College faculty, administrators, and committees have used the information gathered from students in program assessment and enhancement efforts. Longitudinal data collection allows for tracking of changes and interventions.